Adequacy to immunosuppression management guidelines in kidney transplant recipients with severe COVID-19 pneumonia: a practice survey - Jacq, Amélie; Auvray, Christelle; Blot, Mathieu; Bouhemad, Belaïd; Casenaz, Alice; Lamarthée, Baptiste; Legendre, Mathieu; Quenot, Jean-Pierre; Zanetta, Gilbert; Tinel, Claire (Frontiers in Transplantation, 2024)
Coronavirus disease 2019 (COVID-19) poses an important risk of morbidity and of mortality, in patients after solid organ transplantation. Recommendations have been issued by various transplantation societies at the national and European level to manage the immunosuppressive (IS) regimen upon admission to intensive care unit (ICU). The aim of this study was to evaluate the adequacy of IS regimen minimization strategy in kidney transplant recipients hospitalized in an ICU for severe COVID-19, in relation to the issued recommendations. The immunosuppressive therapy was minimized in all patients, with respectively 63% and 59% of the patients meeting the local and european recommendations upon admission. During ICU stay, IS was further tapered leading to 85% (local) and 78% (european) adequacy, relative to the guidelines. The most frequent deviation was the lack of complete withdrawal of mycophenolic acid (22%). Nevertheless, the adequacy/inadequacy status was not associated to the ICU- or one-year-mortality. In this single-center cohort, the only variable associated with a reduction in mortality was vaccination, emphasizing that the key issue is immunization prior to infection, not restoration of immunity during ICU stay.